2013
DOI: 10.1186/1479-5876-11-218
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs induced in melanoma treated with combination targeted therapy of Temsirolimus and Bevacizumab

Abstract: BackgroundTargeted therapies directed at commonly overexpressed pathways in melanoma have clinical activity in numerous trials. Little is known about how these therapies influence microRNA (miRNA) expression, particularly with combination regimens. Knowledge of miRNAs altered with treatment may contribute to understanding mechanisms of therapeutic effects, as well as mechanisms of tumor escape from therapy. We analyzed miRNA expression in metastatic melanoma tissue samples treated with a novel combination regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…We further explored the prognostic value of miR-150–5p , because it is not expressed in melanoma cell lines and short-term cultures (25, 26), but well detected in melanoma tissues measured in this study and others(27, 28), which likely contain mixed cell-type populations. Since miR-150–5p is highly expressed in mature B and T-cells(29, 30), we hypothesized that differences in its expression between primary melanomas of different outcomes may be reflective of tumor infiltrating lymphocytes (TILs), rather than of a tumor-cell intrinsic property.…”
Section: Resultsmentioning
confidence: 99%
“…We further explored the prognostic value of miR-150–5p , because it is not expressed in melanoma cell lines and short-term cultures (25, 26), but well detected in melanoma tissues measured in this study and others(27, 28), which likely contain mixed cell-type populations. Since miR-150–5p is highly expressed in mature B and T-cells(29, 30), we hypothesized that differences in its expression between primary melanomas of different outcomes may be reflective of tumor infiltrating lymphocytes (TILs), rather than of a tumor-cell intrinsic property.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a number of miRNAs have been demonstrated to play key roles in melanoma (4,5). A recent study applied an Illumina next-generation sequencing platform to conduct an in-depth analysis of the miRNA transcriptome in MM with matched normal skin, and demonstrated that miR-203, -204-5p, -205-5p, -211-5p, -23b-3p, -26a-5p and -26b-5p were significantly decreased in MM (6).…”
Section: Introductionmentioning
confidence: 99%
“…The down-regulation of miR-320a has been observed in the blood of several cancers including colorectal cancer [25], gastric cancer [26], and retinoblastoma [27]. Moreover, miR-320a is up-regulated in melanoma cells after treatment with Bevacizumab or Rapamycin + Bevacizumab [28]. miR-134 has been characterized as a tumor suppressor, acting to regulate proliferation, apoptosis, and invasion and migration, in a wide range of cancer types including melanoma [31,32].…”
Section: Discussionmentioning
confidence: 99%